O Curso Normal de 1º Ciclo em Assu/RN (1951-1971) - Dutra, Maria da Conceição Farias da Silva Gurgel (2011)
The aim of this research is the analysis of the history of the Normal Course in the 1st period in Assu, Rio Grande do Norte, since its foundation by the state law no. 621, de 06 December 1951 until its demise, with the implementation of the Course of the Magisterium, by Federal Law 5692 from August 11, 1971. The goal is to answer how it was constituted the operation and the educational practices of this institution, teacher trainers, throughout its existence. For this, we analyze the institution's documents in focus interviews, legislation, of the education, newspapers and books of the season, guiding itself by the studies of Chartier (1991), Elias (2001), Certeau (2001), Frago (1995), Magalhães (2005) and Julia (2001). When dealing with an educational institution, the central category of analysis is the school culture, in which supported the cutting of specific categories of study: the entrance into the Normal Course, the conferring of a degree, the "Normalista Week‖ in Assu and formative elements. The Normal Course from 1st cycle formed teachers in a basic level, differing themselves from schools of teacher education of 2nd Cycle. It was founded in Assu as Regional Training Course and called Ginásio Normal in 1961.In the temporal cut studied, 279 women and 07 men were graduated as Regents of Elementary School, demonstrating a school attended virtually by women. In the narrative, it is restored to the inclusion of female students in the Normal Course, focusing on the processes of registration and the admission exams, graduation events, imbued with discourses on the social role of the teacher and the Party Normalista Week, which valued the sense of belonging with of students to the profession. Through theater plays in the school, of practices forming behaviors and stages of female students in elementary school, training elements are reassembled, demonstrating the discourse of modern education intermingled with the Christian Catholic values of the culture for female education. The reconstruction of the historical identity of this institution sometimes close, sometimes unique, when confronted with other schools of teacher training brings a contribution to the setting of the history of schooling in the state of Rio Grande do Norte